Artificial Intelligence (AI) as the Reflective Partner: Empowering Teachers for Deep Learning Pedagogy - Rahman, Abdul; Nurmahmudah, Fitri; Putra, Eka Cahya Sari; Harsono, Arta Mulya Budi; Dewantara, Brezto Asagi; Arsyad, M. Ziyan Takhqiqi; Alfarisa, Fitri (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore the role of AI as a reflective partner to empower teachers in implementing deep learning pedagogy. The method used is a systematic literature review (SLR) with a PRISMA approach. Data was obtained through article searches in the SpringerLink database using relevant keywords, then filtered based on methodological quality, topic suitability, and publication completeness. A total of 21 selected articles were qualitatively analyzed using Atlas.ti version 24 software to identify codes, categories, and research concept maps. The analysis results revealed five main themes of AI’s role in deep learning pedagogy: (1) AI-Supported Deep Learning Lesson Design, which supports teachers in designing objectives, content, and anticipating learning barriers; (2) AI in Orchestrating Deep Learning Processes, which organizes classroom dynamics through inquiry prompts, multi-representation of concepts, and real-time formative feedback; (3) AI-Augmented Deep Learning Assessment, which strengthens authentic assessment through multi-level rubrics, evidence-based performance analysis, and verification of learning processes; (4) AI-Driven Reflective Teaching Practices, which facilitates data-driven reflection, action planning, and knowledge curation for professional development; and (5) Ethical and Contextual AI Integration, which emphasizes the importance of local context, ethical awareness, and data protection. Based on the findings, it is recommended that teachers receive practice-based training that not only focuses on technical skills but also on integrating AI into deep learning pedagogy principles.